2015
DOI: 10.1002/lno.10229
|View full text |Cite
|
Sign up to set email alerts
|

Paternal energetic investments in copepods

Abstract: Copepod mating is a complex behavioral interplay between males and females. But successful mating also requires a physiological component in terms of egg-and spermatophore production. In striking contrast to the extensive literature on copepod egg production, costs of spermatophore production has largely been ignored. This article explores the energetic demands in male copepod reproduction, testing how food and predation risk influence spermatophore production. Moreover, we analyse swimming behavior to test if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…The magnitude of the difference varies among the three main feeding strategies (Kiørboe ): A non‐motile ambush feeder cannot feed and search mates simultaneously, and the males therefore intermittently sacrifice feeding to engage in fast swimming to search for females with an expected higher predation risk in males than in females (Kiørboe ). In active feeding copepods, on the other hand, males swim and feed simultaneously (Bjaerke et al ) and the conflict between feeding and mate‐finding is less as is the expected difference in predation risk between genders (Van Duren and Videler ; Kiørboe ).…”
mentioning
confidence: 99%
“…The magnitude of the difference varies among the three main feeding strategies (Kiørboe ): A non‐motile ambush feeder cannot feed and search mates simultaneously, and the males therefore intermittently sacrifice feeding to engage in fast swimming to search for females with an expected higher predation risk in males than in females (Kiørboe ). In active feeding copepods, on the other hand, males swim and feed simultaneously (Bjaerke et al ) and the conflict between feeding and mate‐finding is less as is the expected difference in predation risk between genders (Van Duren and Videler ; Kiørboe ).…”
mentioning
confidence: 99%
“…The costs of reproduction are not limited to oocyte development, and recent evidence suggests that spermatophore production may require considerable resource investment in copepods (Bjaerke et al, 2015;Burris & Dam, 2015). Although the typical astaxanthin content of spermatophores is not known, our recent results suggest that it might be coupled to FA allocation (Schneider et al, 2016).…”
Section: Discussionmentioning
confidence: 70%
“…This has, e.g., been observed in mayfly larvae that exhibited only increased short-term drifting behaviour in response to predators (Culp et al, 1991). In fact, many prey animals balance the costs of predator-induced behaviour against other fitness-related activities such as foraging and mating (Bjærke et al, 2016; Lima and Dill, 1990; Sih, 1980). This trade-off often limits the duration of predator-induced behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that predation typically results in reduced activity across most taxa (Åbjörnsson et al, 1997;Ahlgren et al, 2011;Gall and Brodie, 2009;Huryn and Chivers, 1999;Kasumyan, 2022;Schäffer et al, 2013;Williams and Moore, 1982;Wisenden et al, 1997), although some, particularly Baetidae, also exhibited increased drift and movement (Culp et al, 1991;Lancaster, 1990;Poff et al, 1991). Similarly, studies found microcrustaceans either decreasing their activity (Bjaerke et al, 2016;Heuschele et al, 2020) or seeking refuge through vertical and horizontal migration (Jack et al, 2006;Lauridsen and Lodge, 1996;Pasternak et al, 2006;Zaret and Suffern, 1976). However, many of these studies focused on only a few select taxa with limited numbers of individuals, potentially obscuring density and biotic interaction effects (Peacor and Werner, 1997;Tollrian et al, 2015).…”
Section: Predator-induced Behaviourmentioning
confidence: 99%